HISTORY OF SAMARKAND SUGD IN CHINESE SOURCES - Indiaminova Shoira Amriddinovna (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
This article highlights the role of Sughd settlements in Sughd’s relations with East Turkestan and China, trade priorities of Sughd in relations with East Turkestan and China. In addition to this, the following issues, the historical basis of the relations between Sughd and China, the location of the Sughds in China and Eastern Turkestan, a general description of the trade relations in the Sughd settlements in Eastern Turkestan, the role of the Sughd settlements in the trade and political relations between Sughd and China, the early medieval East Turkestan and China relations with reflected in the sources illuminated on a scientific basis .